A STUDY ON FACTORS AFFECTING DIGITAL CITIZENSHIP AMONG COLLEGE FACULTIES IN INDIA - Hussainy, Syed Sadullah; Jamalullah, R Syed (PUPIL: International Journal of Teaching, Education and Learning, 2021)
Digital citizenship is described as the conscientious use of technology by some who interacts with society at various levels such as social, financial, political, and governmental etc., by using computers, internet, and the digital devices. The Digital citizens practice the safe, respectful, and lawful use of technology by understanding the rights and responsibilities when he/she is online. This research helps the faculties to understand what they should be aware of while using digital technologies. This paper is mainly addressing three important factors that affect digital citizenship among colleges and universities faculties, i.e., 1. Internet knowledge, 2 Attitudes towards internet and 3. Computer self-efficacy. The qualitative research approach was adopted, where the objects are one hundred and fifteen universities and colleges professors from the south Indian region. The result of this research reveals that faculties’ digital citizenship is roughly at a good level. Apart from this, computer literacy and computer experience may not be affecting the digital citizenship among universities and college faculties. Faculties who have studied and got training in computer-related courses and having valid credential like and prefer to engage in self-education and online events. The Internet attitude and self-efficacy of computers have driven a higher degree of global citizenship. Finally, for the faculty of universities/colleges, different suggestions were made to develop digital citizenship.